Sintesis Etil 4-(3,5-dimetil-4-fenoksifenil)-6-metil-2-okso-1,2,3,4-tetrahidropirimidin-5-Karboksilat dan Uji Aktivitas Sitotoksik Terhadap Sel T47D - Maulina, Fariha Mufidah; Fauzi, Ahmad; Ramadhan, Muhammad Reza; Hakimah, Wafiq Kholifatul (Journal of Pharmaceutical and Sciences, 2025)
Cancer is one of the biggest health problems in the world, including in Indonesia. Previous studies have found that DHPM compounds have various pharmacological activities such as anticancer, antifungal, antibacterial, antituberculosis, and antioxidant. Based on this potential, it is interesting to conduct further research with the aim of synthesizing and developing new Dihydropyrimidinone (DHPM) compound derivatives that have potential as anticancer. The synthesis of DHPM derivatives was carried out to obtain ethyl 4-(4-hydroxy-3,5-dimethylphenyl)-6-methyl-2-oxo-1,2,3,4-tetrahydropyrimidine-5-carboxylate (M1). Then the compound was developed by Mitsunobu reaction using a sonicator to obtain a new compound ethyl 4-(3,5-dimethyl-4-phenoxyphenyl)-6-methyl-2-oxo-1,2,3,4-tetrahydropyrimidine-5-carboxylate (C2) which will be tested for cytotoxic activity against T47D cancer cells. Characterization of the compound was done using FT-IR, LC-MS, and melting point. Cytotoxic test against T47D cells as anticancer agent using MTT method [3-(4,5-dimethylthiazol-2-yl)-2,5 diphenyltetrazolium bromide] assay. The test results of compound C2 had cytotoxic activity with IC50 of 202.22 µg/mL. The results showed that compound C2 has cytotoxic activity but it is mild because the IC50 produced is high. These findings suggest that compound C2 has anticancer potential, but further structure optimization is needed to increase its effectiveness.